Psychological resilience: the role of unconscious and conscious coping strategies in the mediation of stress in high risk occupational contexts - Alexander, Debra Geraldine (Rhodes University, Faculty of Humanities, Department of Psychology, 2002)
This study investigates the role of unconscious and conscious coping strategies in the mediation of stress in high risk occupational contexts. The Social Readjustment Rating Scale, the Multidimensional Coping Inventory and the Defense Style Questionnaires were completed by 194 police, ambulance and teaching personnel. A sample of 37 teachers served as a non high risk occupation control group. Descriptive statistics, regression analysis, analysis of variance, analysis of difference and principal component analysis were performed on the data. Results indicated minimal significant between group differences. Within group variances were yielded. A minor relationship between levels of stress and usage of positive and negative mechanisms was observed. The significance of these findings is discussed and recommendations made for further study.
Keywords: Hazardous occupations; Teachers -- South Africa -- Job stress; Police -- South Africa -- Job stress; Emergency medical personnel -- South Africa -- Job stress; Stress (Psychology)